Prediction of Left Double-Lumen Tube Size by Measurement of Cricoid Cartilage Transverse Diameter by Ultrasound and CT Multi-Planar Reconstruction - Zhang, Chengchao; Qin, Xinlei; Zhou, Wenyi; He, Shuaijie; Liu, Ao; Zhang, Yu; Dai, Zhigang; Yin, Jiangwen (Frontiers in Medicine, 2021)
Currently, there is no uniform standard for selecting the double lumen tubes (LDLT). The ultrasonic and computed tomography (CT) multi-planar reconstruction (MPR) technology will certainly provide more accurate measurement. For better application in clinical anesthesia for thoracic surgery choice of double lumen tube intubation, reducing the complications, this study aimed to compare the two approaches. In the first part, 120 cases of single lung ventilation and patients who met the inclusion and exclusion criteria, the LDLT was selected according to the height and gender; and to record the patient's optimum LDLT and collect the transverse diameter of the cricoid cartilage (TD-C) ultrasound and CT MPR patient data, obtain the corresponding different types of LDLT ultrasound and CT MPR measurement of the TD-C range. Second part was divided into a randomized double-blind prospective study. 102 patients were randomly divided into the ultrasound group and the CT MPR group. TD-C was measured by ultrasound, and the corresponding type for intubation was selected and its accuracy was judged based on the conclusions derived from the first part. In CT MPR group, TD-C was measured by CT MPR, and the corresponding type for intubation was selected and its accuracy was judged based on the conclusions derived from the first part. The success rate of intubation was recorded, and the accuracy of the LDLT was compared between the two groups. No significant difference in the distribution of the proportion of each type of LDLT between Ultrasonic group and CT MPR group(P > 0.05). The accuracy rate of intubation in the ultrasound group was 90.2% and the corresponding rate in the CT MPR group was 94.1%, with no significant difference in intubation accuracy between the two groups (P > 0.05). The accuracy of selecting the LDLT based on TD-C measured by ultrasound and CT MPR is higher than the traditional experience; it can significantly reduce the perioperative complications and there is no statistical difference in the accuracy of selecting the LDLT by ultrasound and CT MPR.